Influence on Postural Sway Immediately after Standing on a Sloping Platform: Comparison of Hemiplegic Patients with Healthy Adults - ABO, Masahiro; NAKAYAMA, Yasuhide; IIJIMA, Setu (Rigakuryoho Kagaku, 2008)
[Purpose] We examined the influence on postural sway while standing on level ground after standing on a sloping platform. [Subjects] The subjects were 24 people (8 young adults, 8 middle-aged people and 8 hemiplegia patients). [Methods] The subjects stood on a 10-degree sloping platform for one minute. The center of foot pressure and postural sway area were measured before and after the intervention. [Results] The forward shift of center of foot pressure on level ground after the intervention was confirmed as an immediate reaction. [Conclusion] In comparison of the measurements at 5, 10, and 15 minutes after the intervention, it was observed that the forward shift of center of foot pressure due to the righting reflex remained intact.